Synaptic GAP and GEF Complexes Cluster Proteins Essential for GTP Signaling - Brent Wilkinson (Nature Portfolio, 2017)
Abstract GTPase-activating proteins (GAPs) and guanine exchange factors (GEFs) play essential roles in regulating the activity of small GTPases. Several GAPs and GEFs have been shown to be present at the postsynaptic density (PSD) within excitatory glutamatergic neurons and regulate the activity of glutamate receptors. However, it is not known how synaptic GAP and GEF proteins are organized within the PSD signaling machinery, if they have overlapping interaction networks, or if they associate with proteins implicated in contributing to psychiatric disease. Here, we determine the interactomes of three interacting GAP/GEF proteins at the PSD, including the RasGAP Syngap1, the ArfGAP Agap2, and the RhoGEF Kalirin, which includes a total of 280 interactions. We describe the functional properties of each interactome and show that these GAP/GEF proteins are highly associated with and cluster other proteins directly involved in GTPase signaling mechanisms. We also utilize Agap2 as an example of GAP/GEFs localized within multiple neuronal compartments and determine an additional 110 interactions involving Agap2 outside of the PSD. Functional analysis of PSD and non-PSD interactomes illustrates both common and unique functions of Agap2 determined by its subcellular location. Furthermore, we also show that these GAPs/GEFs associate with several proteins involved in psychiatric disease.